MENGOPTIMALKAN LITERASI ALQURAN: MENGEKSPLORASI STRATEGI PEDAGOGIS DAN FAKTOR-FAKTOR SOSIAL-LINGKUNGAN YANG BERDAMPAK PADA KEMAHIRAN MEMBACA AL-QURAN DI KALANGAN SISWA MADRASAHTSANAWIYAH AL-IHSAN TANAH GROGOT - Annisa Mae Dilla; Adiyono Adiyono (CV. ADIBA ASIHA AMIRA, 2025)
This research was conducted because it is important for every individual to have the ability to read the Al-Qur'an, as well as study and understand the laws of reading the Al-Qur'an, but in reality there are still students who are not able to read the Al- Qur'an. Therefore, it is necessary to conduct research with the aim of finding out the efforts of Al-Qur'an Hadith teachers in improving the ability to read the Al-Qur'an in class VIIB students at Mts Al-Ihsan Tanah Grogot and the factors that influence improving the ability to read the Al-Qur'an. an Shiva class VIIB Mts Al-Ihsan Tanah Grogot. This research is qualitative research, the instruments used in data collection are: observation, interviews and documentation. The data analysis used is data processed using qualitative analysis through the stages of data reduction, data display and conclusions. Based on the results of research and analysis, it is concluded that the Al-Qur'an Hadith teacher's efforts to improve students' ability to read the Al- Qur'an is by frequently reading the Al-Qur'an repeatedly and understanding the contents of the Al-Qur'an and pay attention to each tajwid reading in the Qur'an. And the factors in improving students' ability to read the Koran, namely supporting and inhibiting factors, are parental support and support from the surrounding environment.